ICT Classes at the DIET College Mahbubnagar: Bringing Digital Skills for Both Men and Women in DIET College - Sana Tahniyath; Srinivas Akula; Radhika Iyengar (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
The District Institutes of Education and Training (DIETs) are responsible to train all pre- primary and primary school teachers in India. Each district has a DIET that is required to provide a certification program for all the potential primary teachers in the district. As a part of the State wide curriculum followed by DIET, a course on ICT is mandatory for all teachers. Trainees. CSD had already developed an ICT curriculum at a community-based ICT center. Given the needs of the DIET, the Center started to support the ICT lab at the DIET. The project will start with a pilot in Mahbubnagar which will be helpful to prepare a generic model for the country. This initiative will re-active the ICT lab that each DIET has. The work thus initiated will help to implement the SCERT prescribed ICT Curriculum in the DIET. This report provides an overview of the work completed in the first 5 months of intervention. It then outlays the new suggested chnages for the 2019-20 academic year.
Keywords: 330